The influence of dietary protein levels on growth curve parameters of quail - Kellerman, Stephanie; Schoeman, S. J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Agrisciences)--University of Stellenbosch, 2004.